"Compulsive exercise is a socially acceptable prison cell": Exploring experiences with compulsive exercise across social media. Issue 9 (13th July 2021) - Hallward, Laura; Duncan, Lindsay R.
Abstract: Objective: Investigations into online eating disorder (ED) communities have allowed for a rich exploration of lived experiences focused on a number of aspects, such as recovery and support groups. There is a lack of understanding around compulsive exercise (CE), which is often a characterizing condition of EDs. Exploring the lived experiences of CE as discussed online could provide helpful insight towards a better understanding of CE. Therefore, the purpose of this study was to explore experiences around CE and EDs shared on social media sites. Method: Social media posts related to CE and EDs from Reddit, Twitter, Instagram, and forums were collected for 12 months. A thematic analysis of 881 posts was used to identify common themes among individuals' lived experiences with CE. Results: Five themes (and three subthemes) were identified across the social media posts: (1) seeking control, but ultimately CE takes hold, (2) burning off binges, but at what expense?, (3) recovery is a battle, but worth it, (4) is my exercise healthy?, and (5) frustration with comments about CE. Discussion: The lived experiences of CE among individuals with EDs have provided support for current definitions of CE and shared novel insight into the recovery experience. Individuals online also highlighted the need for improvement in treatment around CE specifically, and greater awareness around CE for the general public and healthcare providers.